2016
DOI: 10.1139/gen-2015-0228
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative protocol for DNA metabarcoding of springtails (Collembola)

Abstract: Abstract:We developed a novel protocol with superior quantitative analysis results for DNA metabarcoding of Collembola, a major soil microarthropod order. Degenerate PCR primers were designed for conserved regions in the mitochondrial cytochrome c oxidase subunit I (mtCOI) and 16S ribosomal RNA (mt16S) genes based on published collembolan mitogenomes. The best primer pair was selected based on its ability to amplify each gene, irrespective of the species. DNA was extracted from 10 natural communities sampled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 64 publications
0
40
1
Order By: Relevance
“…Instead, position and type of mismatch can have widely different effects on amplification efficiency (Kwok et al 1990). Nevertheless, the accurate quantification of relative abundances of taxa is critical for many biodiversity analyses, and much effort is therefore being made to optimize methods for quantitative metabarcoding (Krehenwinkel et al 2017a;Piñol et al 2019;Saitoh et al 2016).…”
Section: Quantitative Metabarcoding and Pcr-free Metagenomicsmentioning
confidence: 99%
“…Instead, position and type of mismatch can have widely different effects on amplification efficiency (Kwok et al 1990). Nevertheless, the accurate quantification of relative abundances of taxa is critical for many biodiversity analyses, and much effort is therefore being made to optimize methods for quantitative metabarcoding (Krehenwinkel et al 2017a;Piñol et al 2019;Saitoh et al 2016).…”
Section: Quantitative Metabarcoding and Pcr-free Metagenomicsmentioning
confidence: 99%
“…For example, it is generally difficult to determine the geographic provenance of a sample with DNA barcoding, which could be useful for uncovering illegal fishing or protected designation of origin substitutions, although some populations do contain distinct COI sequences (Bogdanowicz et al 2000). Inferring data on biomass from copy numbers of sequences is still contentious (Deagle et al 2013) and the subject of system-specific research (Saitoh et al 2016), so frauds such as product dilution will be difficult to detect.…”
Section: Preventing the Mislabelling Of Food Productsmentioning
confidence: 99%
“…Some studies have shown that eDNA extracted from water is a good indicator of relative species abundance in aquatic systems (Lodge et al 2012;Thomsen et al 2012;Pilliod et al 2014), and while this provides a good starting point, it remains a thorny issue for terrestrial systems (Saitoh et al 2016), for invertebrate species (due to primer bias), or when degraded DNA is used (King et al 2008). One solution is to model occupancy (species-level) or spatial mark-recapture (individual-level) data, although careful experimental designs are needed before data collection can begin (Schnell et al 2015).…”
Section: Issues and Implementationmentioning
confidence: 99%
“…However, quantification of organismal abundance via metabarcoding and HTS has remained an underdeveloped area of methodological study. In this special issue, Saitoh et al (2016) present a novel protocol employing HTS for the quantification of springtail (Collembola) communities, which form an important component of the soil biota. Using natural and artificially constructed test communities, the authors find that reliable quantification is possible under standardized molecular conditions involving the inclusion of a known species as an internal control.…”
Section: Advances In Quantificationmentioning
confidence: 99%
“…The current open-access special issues feature 24 full articles. Part 1 includes two reviews that expand upon conference presentations and themes and 10 additional research articles associated with conference presentations, four of which are first authored by winners of a postdoctoral or graduate student prize at the 6th Conference (Beet et al 2016;Mark et al 2016;Saitoh et al 2016;Sing et al 2016). Part 2 includes 12 additional articles-three reviews, eight research articles, and one opinion piece-that cover topics ranging from a review of the field of fungal DNA barcoding (Xu 2016) to applications of DNA barcoding for biosecurity (Hodgetts et al 2016) to multiple novel methods of species detection (discussed below).…”
Section: Introductionmentioning
confidence: 99%